Effects of Nb2O5 and Gd2O3 doping on boron volatility and activity between glass seals and lanthanum-containing cathode - Zhang, Q.; Chen, Kongfa; Tang, D.; Zhang, T.; Jiang, San Ping (Elsevier Ltd, 2017)
In planar Solid Oxide Fuel Cells (SOFCs), the boron species volatilize from glass seals, and react with lanthanum-containing cathodes (i.e., La0.6Sr0.4Co0.2Fe0.8O3 - d, LSCF) to form LaBO3 under cathodic polarization, which decomposes the perovskite structure and consequently decreases the electrochemical activity of cathode. In this study, Nb2O5 and Gd2O3 are added to an aluminoborosilicate glass to reduce the boron volatility from glass and the reaction between sealing glass and LSCF cathode. Both Nb2O5 and Gd2O3 doping increases the network connectivity, but Nb2O5 doping enhances the [BO3] ? [BO4] transition and reduces the boron volatility from glass seals, thus effectively suppressing the deposition and poisoning of boron contaminants on the LSCF cathode. However, an obvious degradation of the electrocatalytic activity of LSCF occurs in the presence of Gd2O3-doped glass. The relationship between glass structure and glass/cathode interaction has been established to provide useful information for designing stable sealing materials for SOFC applications.